- PENGARUH FINTECH TERHADAP KINERJA KEUANGAN PERBANKAN SYARIAH: - - , Winda Sari Siregar, Nurul Madaniah Ayla, Sry Lestari (Islamic Circle, 2021)
This study aims to determine the effect of fintech on the financial performance of Islamic banking listed on the OJK 2021. The data analysis technique used is multiple linear regression with the SPSS application. Based on the results of the analysis, fintech services can improve banking financial performance. Researchers use ROA, BOPO, NPL, to measure financial performance Keywords: Fintech, BOPO, NPF, ROA.